Features of surgical and endovascular procedures in adults with congenital heart defects - Lebid, I. H.; Rudenko, N. M.; Liebied, Y. I.; Kuzmenko, Yu. L. (Ukrainian Journal of Cardiovascular Surgery, 2018)
Annual increase the number of interventions in adults with congenital heart defects (ACHD) requires the estimation of long-term follow up surgical and interventional treatment strategies for this pathology. The goal was to estimate different strategies for cardiac surgery care in ACHD Matherial and Methods. This retrospective review included an analysis of medical case reports of all patients aged 18 years and older during period from 01 Jan 1999 to 31 Dec 2015. There were 3 periods: Period 1 – from 1999 to 2005, Period 2 – from 2006 to 2010, Period 3 – from 2011 to 2015. 450 surgical procedures were performed in 382 patients over the study period. Mean age at the time of intervention was 31.7±0.7 years; 18–87 years), 190 (50%) male, 192 (50%) – female. Results and discussion. At the beginning of research 100% interventions for adults with simple CHD (ASD, VSD, PDA) were surgical, with increasing amount endovascular interventions till 35% in follow period. At the 3 period 54% patients with Coarctation of aorta had endovascular interventions. There was prevalence number of patients with conduit pathology after endovascular interventions in 2 period (67%) and 3 period (53%) compared with surgery strategy. Conclusions There was increasing the number of endovascular intervention in adults with simple CHD, coarctation of aorta and conduit pathology with good postoperative follow-up period, what takes this strategy into the first place in cardiac care system for these patients.